Pharmacognostic Profile and Pharmacological Activity of different parts of Amorphophallus campanulatus (Roxb.) Blume- A Complete Overview. - Mallik, Jony; Das, Joyeta; Banik, Rony Kumar (Asian Journal of Pharmaceutical Research and Development, 2018)
Amorphophallus campanulatus (Roxb.) Blume is a valuable corm producing plant in the world. It is most commonly named as Elephant foot yam. Among all species of Amorphophallus, Amorphophallus campanulatus (Roxb.) has good medicinal value. Amorphophallus campanulatus (Roxb.) is growing widely throughout the Bangladesh (Forests of Gazipur, Sherpur, Chittagong, Chittagong Hill Tracts, Cox’s Bazar, Tangail and planted elsewhere). It is largely cultivated in the Philippines, Java, Indonesia, Sumatra, Malaysia, India and China 14. In Bangladesh, it is called as Ol, Olkachu 15. Indian subcontinent, Sri Lanka and Apparently cucumbers have originated in the foothills of the Himalayan mountains, just north of the Bay of Bengal, the area which is now primarily occupied by Bangladesh. As it is a tuberous crop plant, many of the chemical constituents found in its corm. This plant contains vast of important phytochemical constituents whose are able to provide desired pharmacological response.The main goal of this paper is to make a proper status of about pharmacognostic profile and pharmacological activity of Amorphophallus campanulatus(Roxb.) Blume.